2023
DOI: 10.14218/csp.2022.00019
|View full text |Cite
|
Sign up to set email alerts
|

Nutri-phenethyl Isothiocyanate Jelly Promotes Detoxification of a Tobacco-specific Oral Carcinogen in Male Active Cigarette Smokers

Abstract: Background and objectives: Phenethyl isothiocyanate (PEITC), a phytochemical from cruciferous vegetables, is known to modulate detoxification enzymes. Fortification of PEITC into a complete nutrition gel, Nutri-PEITC jelly, has been shown to improve its bioavailability. This work aimed to study the effect of Nutri-PEITC jelly on active smokers' detoxification of tobacco-derived carcinogens.Methods: This pre-post trial was conducted on 30 healthy, male, regular smokers. During the pre-intervention period, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several previous studies have found that ITCs can inhibit the development of cancer in a variety of organs in animal models, including oral, prostate, breast, colon, lung, gastric, and liver [5][6][7]. Clinical trials showed that ITCs can promote detoxification and urinary excretion of tobacco-derived and grilled meat-derived carcinogens [8][9][10]. Case-control and cohort studies also found that consumption of Brassica vegetables is associated with decreased risk of several types of cancer [11][12][13].…”
Section: Introductionmentioning
confidence: 93%
“…Several previous studies have found that ITCs can inhibit the development of cancer in a variety of organs in animal models, including oral, prostate, breast, colon, lung, gastric, and liver [5][6][7]. Clinical trials showed that ITCs can promote detoxification and urinary excretion of tobacco-derived and grilled meat-derived carcinogens [8][9][10]. Case-control and cohort studies also found that consumption of Brassica vegetables is associated with decreased risk of several types of cancer [11][12][13].…”
Section: Introductionmentioning
confidence: 93%
“…An intensive reading of the "Nutri-phenethyl Isothiocyanate Jelly Promotes Detoxification of a Tobacco-specific Oral Carcinogen in Male Active Cigarette Smokers" study, highlights that the authors constructed a PEITC fortification that generated a complete nutrition gel (Nutri-PEITC). 3 The result was that the Nutri-PEITC jelly significantly increased the level of total urinary concentration of a tobacco-specific oral carcinogen, n-nitrosonornicotine (NNN) metabolite, enhancing its detoxification by promoting glucuronide conjugation. The authors also discussed and explained that the detoxification mechanisms of Nutri-PEITC Jelly may be metabolized and ultimately eliminated through the urine of xenobiotics, on both phases I and II drug-metabolizing enzymes.…”
mentioning
confidence: 99%